الكفاءة الاقتصادية لمزارع تسمين الخراف في محافظة حمص - النمر, فاتن; يعقوب, غسان; عباس, حسان (Latakia University Journal -Biological Sciences Series, 2014)
هدفت الدراسة إلى تقييم الكفاءة الاقتصادية لمزارع تسمين الخراف في محافظة حمص ودراستها خلال الفترة 2008-2013 حيث أجريت الدراسة على عينة تضم 25 مزرعة، متوسط عدد الخراف فيها نحو 25 رأس من العواس، من خلال حساب التكاليف والإيرادات، وباستخدام بعض المؤشرات الاقتصادية. وقد أظهرت النتائج أن متوسط الإيرادات قبل الأزمة بلغ نحو 3743138 ل.س، وخلال الأزمة نحو 690525 ل.س، في حين بلغ متوسط كلفة إنتاج 1 كغ من الوزن القائم للخروف نحو 159 ل.س قبل الأزمة، ونحو 343 ل.س خلال الأزمة، كما بلغ متوسط الربح السنوي الصافي قبل الأزمة نحو 427017 ل.س، وخلال الأزمة نحو 543224 ل.س. أما متوسط هامش صافي الربح قبل الأزمة فقد بلغ نحو 38 %، وخلال الأزمة نحو24.6 %، وبلغ متوسط العائد لكل وحدة إنفاق (معدل العائد البسيط) قبل الأزمة نحو1.6 ل.س/وحدة انفاق، ونحو 1.4خلال الأزمة، وبلغ متوسط الربحية بالقياس لرأس المال المستثمر قبل الأزمة نحو 106.3%، ونحو 69.7% خلال الأزمة. وفيما يتعلق بمتوسط الربحية بالقياس لتكاليف الإنتاج قبل الأزمة فقد بلغ نحو 61.8%، و 39.5% خلال الأزمة، في حين بلغ متوسط زمن استعادة رأس المال المستثمر قبل الأزمة نحو 1.7 سنة، ونحو 2.8 سنة خلال الأزمة. كما بينت نتائج البحث انتشار العديد من الأخطاء الشائعة بين المربين القائمين بعملية التسمين، منها استخدام نفس تركيبة العلف طول فترة التسمين، وعدم الالتزام بإعطاء اللقاحات، وعدم صناعة الدريس و السيلاج، وشراء معظم الأعلاف من السوق السوداء، مما يجعل المسمنين عرضة لاحتكار التجار. الأمر الذي يستوجب تدخلاً سريعاً وأكثر فاعلية للتوسع في إنتاج اللحوم الحمراء، وأن يكون ذلك مشمولاً بالخطط التنموية للدولة، والعمل على حماية خراف القطر و منع تهريبها، وتقديم الدعم والتشجيع اللازم للمربين ليمارسوا مهنة التسمين، خاصة بعد عزوف قسم منهم عن هذه المهنة خلال الأزمة، والعمل على توعية المسمنين على ضرورة استخدام طرق تسمين أفضل، وإجراء كل ما يلزم لتنمية هذا القطاع الإنتاجي المهم . The study aimed at evaluating and studying the economic efficiency of farms fattening sheep in Homs during the period (2008-2013), where the study was conducted on a sample of 25 farms, the average number of sheep, where about 25 head of Awas, by calculating the costs and revenues, and using some of the economic indicators, where The results showed the following:The average revenue before the crisis to about 3743138 sp , and during the crisis to about 690525 sp.The average cost of producing 1 kg of gross weight of the animal for 159 sp before the crisis , and about 343 sp during the crisis .The average annual net profit before the crisis to about 427017 sp, and during the crisis to about 543224 sp.The average net profit margin before the crisis has reached about 38%, and during the crisis, about 24.6%, and reached average income per unit spending (rate of return simplex) before the crisis about 1.6 /unit spending, and about 1.4 /unit spending during the crisis. The average Profitability Coefficient for the capital invested by the crisis reached about 106.3%, and about 69.7 % during the crisis, but for the average coefficient profitability for the pre-crisis production costs have reached about 61.8%, and 39.5% during the crisis, the average time of the restoration of the invested capital before the crisis reached about 1.7 years, about 2.8 years during the crisis. The study also demonstrated an outbreak many of the mistakes common among farmers like to use the same combination of feed during the grow-out period and the lack of commitment by giving vaccines and not making Aldrees and silage and fodder buy most of the black market, which makes farmers vulnerable to the monopoly of the merchants. Which requires urgent intervention and more effective in order to expand the production of red meat, and to be covered by the development plans of the state, and work to protect the sheep of the country and prevent smuggling and to provide support and encouragement necessary for farmers to practice their profession fattening, especially after the reluctance of some of them for this the profession during the crisis, and working to educate farmers on the need to use methods of fattening more economically feasible, and conducting all necessary for the development of this important productive sector.